Keterlibatan ayah dalam perawatan bayi baru lahir untuk meningkatkan kedekatan: A systematic review - Dewi, Prita Ayu Kusuma; Rachmawati, Imami Nur; Ungsianik, Titin (Holistik Jurnal Kesehatan, 2025)
Background: Fathers’ involvement in newborn care is very important in influencing newborns’ behavior, psychology, and overall health. Fathers who are involved in care have more positive feelings about their interactions with their babies, understand and appreciate their babies more, and develop meaningful bonds with their babies. Purpose: To identify the influence of the father's role in early infant care to increase closeness. Method: A systematic review using the PRISMA format, obtained from 7 databases, namely Pubmed, Sage, Sciencedirect, Proquest, Scopus, Springer, Wiley and Taylor & Francis online with the keywords Father Involvement OR Father Involvement OR Involved Fathers AND Parents OR Male partners OR Fathers OR Fathers AND Attachment binding Newborn OR Father-infant bonding. OR selected infant temperament articles were screened based on a five-year period and in English. Critical appraisal analysis was performed using the JBI format. Fifteen articles containing 1,776 fathers involved in newborn care were obtained. Results: The relationship or bond becomes closer between the father and his baby. The involvement of the father in newborn care significantly increases the presence of follow-up in conducting clinical examinations on babies at health facilities and shortens the length of stay in the hospital, and increases the survival of newborns. Conclusion: Fathers who are involved in newborn care have more positive feelings about their interactions with their babies, understand and appreciate their babies more, and develop meaningful bonds with their babies.   Keywords: Closeness; Father involvement; Newborn care.   Pendahuluan: Keterlibatan ayah dalam perawatan bayi baru lahir sangat penting dalam memengaruhi perilaku, psikologis, serta kesehatan bayi baru lahir secara keseluruhan. Ayah yang terlibat dalam perawatan lebih memiliki perasaan positif tentang interaksi mereka dengan bayinya, lebih memahami, dan menghargai bayi mereka dan mengembangkan ikatan yang bermakna dengan bayinya. Tujuan: Untuk mengidentifikasi pengaruh peran ayah dalam perawatan bayi pada masa awal untuk meningkatkan kedekatan. Metode: Systematic review menggunakan format PRISMA, didapatkan dari 7 database, yaitu Pubmed, Sage, Sciencedirect, Proquest, Scopus, Springer, Wiley dan Taylor & Francis online dengan kata kunci Paternal Involvement OR Keterlibatan Ayah OR Involved Fathers AND Parents OR Male partner OR Fathers OR Ayah AND Bounding attachment Bayi baru lahir OR Ikatan antara ayah-bayi. OR infant temperament artikel yang dipilih telah diskrining berdasarkan kurun waktu lima tahun dan berbahasa Inggris. Analisis critical appraisal dilakukan dengan menggunakan format JBI. Diperoleh 15 artikel yang menyertakan 1,776 ayah yang terlibat dalam perawatan bayi baru lahir. Hasil: Hubungan atau ikatan menjadi lebih dekat/erat antara ayah dan bayinya. Keterlibatan ayah dalam perawatan bayi baru lahir secara signifikan meningkatkan kehadiran tindak lanjut dalam melakukan pemeriksaan klinis pada bayi di fasyankes serta memperpendek masa tinggal di rumah sakit, dan meningkatkan kelangsungan hidup bayi baru lahir. Simpulan: Ayah yang terlibat dalam perawatan bayi baru lahir lebih memiliki perasaan positif tentang interaksi mereka dengan bayinya, lebih memahami, dan menghargai bayi mereka dan mengembangkan ikatan yang bermakna dengan bayinya.   Kata Kunci: Keterlibatan Ayah; Perawatan Bayi Baru Lahir; Kedekatan.